Estimated Numbers of Community Cases of Illness Due to Salmonella, Campylobacter and Verotoxigenic Escherichia Coli: Pathogen-Specific Community Rates. Issue 4 (1st August 2006) - Thomas, M Kate; Majowicz, Shannon E; Sockett, Paul N; Fazil, Aamir; Pollari, Frank; Doré, Kathryn; Flint, James A; Edge, Victoria L
Abstract : OBJECTIVE: To estimate the annual number of cases of illness due to verotoxigenic Escherichia coli (VTEC), Salmonella and Campylobacter in the Canadian population, using data from the National Notifiable Disease registry (NND), estimates of under-reporting derived from several National Studies on Acute Gastrointestinal Illness, and the literature. METHODS: For each of the three pathogens (VTEC, Salmonella and Campylobacter ), data were used to estimate the percentage of cases reported at each step in the surveillance system. The number of reported cases in the NND for each pathogen was then divided by these percentages. In cases where the pathogen-specific estimates were unavailable, data on acute gastrointestinal illness were used, accounting for differences between those with bloody and nonbloody diarrhea. RESULTS: For every case of VTEC, Salmonella and Campylobacter infection reported in the NND, there were an estimated 10 to 47, 13 to 37, and 23 to 49 cases annually in the Canadian population, respectively. CONCLUSIONS: The authors estimate that a significant number of infections due to VTEC, Salmonella and Campylobacter occur each year in Canada, highlighting the fact that these enteric pathogens still pose a significant health burden. Recognizing the significant amount of under-reporting is essential to designing appropriate interventions and assessing the impact of these pathogens in the population.